ADVANTAGE AND DISADVANTAGES OF ONLINE EDUCATION (Ustozlar uchun, 2025)
This research explores the dual impact of online education, focusing on its strengths and weaknesses. Digital platforms provide learners with flexible study options, broad access to academic resources, and reduced financial costs. At the same time, challenges such as limited human interaction, motivational decline, and technical barriers persist. The paper argues that combining online and traditional methods is essential for achieving effective and sustainable learning outcomes.